Anaemia in Trimester III Pregnant Women Unrelated with LBW Incidence - Dyah Ekowati (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Anaemia is a decrease in red blood cells or hemoglobin so that it is unable to supply oxygen to the tissues. One of the effects of anaemia in pregnancy is LBW. Data at the Bungatan Health Center, namely 29.1% of babies born with LBW. The incidence of LBW should be 7.5% of the IDHS. The aim of the study was to determine the relationship between anaemia in third trimester pregnant women and the incidence of LBW at the Bungatan Health Center, Situbondo Regency. The research design is an analytical survey using a "retrospective" approach. The population was mothers who were >36 weeks' gestation who gave birth to LBW babies or not and detected third trimester Hb levels and did not experience pregnancy pathology. Samples were taken by "Simple Random Sampling" namely 109 of 149 mothers giving birth. The independent variable is anaemia in pregnancy and the dependent variable is LBW. The research data is secondary medical record data analyzed using the chi square test, α = 0.05. Statistical test results x² count = 1.629 < x² table = 3.481 so Ho is accepted, meaning that there is no relationship between anaemia in third trimester pregnant women and low birth weight babies. The conclusion of the study is that there was no relationship between anaemia in third trimester pregnant women and low birth weight babies because there are many factors that cause low birth weight babies, so further research is recommended on other factors that influence low birth weight births.